PERSEPSI GURU TERHADAP PENILAIAN AUTENTIK PADA KURIKULUM 2013 DI SEKOLAH DASAR KECAMATAN BAJENG KAB. GOWA (JS (JURNAL SEKOLAH), 2022)
Abstract: Teachers Perceptions on Authentic Assessments in Curriculum 2013 at Elementary Schools in Bajeng District, Gowa regency. The study aims to describing teachers™ perceptions of authentic assessments in the 1013 curriculum and to identify supporting factors and inhibits teachers in conducting authentic assessments in the 2013 curriculum. This research uses a type of qualitative descriptive research using observation, interview, and documentation techniques. The data analysis techniques used ere data reduction, data presentation, and conclusion withdrawal.. The results showed that teachers perceived authentic assessment as a fairly good assessment system. The teacher stated that by conducting authentic assessments we could assess the ability of learners as a whole part, not only in the realm of knowledge of learners but also in the realm of attitudes and skills of learners. Supporting factors included the existence of motivation, the existence of cooperation between teachers, the realization of a conducive learning environment, the readiness of learners in learning, teacher understanding and mastery, completeness of facilities and infrastructure, KKG (teacher working group), support from the principal and supervisor. Inhibiliting factors included time constraints in assessing, too many learning devices that must be arranged, lack of motivation of learners in learning, the existence of some teachers who have not mastered IT, the lack of socialization of 2013 curriculum, lack of availability of facilities and infrastructure.     Keywords: authentic Assessment, 2013 Curriculum. Abstrak: Persepsi Guru Terhadap Penilaian Autentik pada Kurikulum 2013 di Sekolah Dasar Kecamatan Bajeng Kabupaten Gowa. Penelitian ini bertujuan untuk mendeskripsikan persepsi guru terhadap penilaian autentik pada kurikulum 2013 serta untuk mengidentifikasi faktor pendukung dan penghambat guru dalam melakukan penilaian autentik pada kurikulum 2013. Penetilian ini menggunakan jenis penelitian deskriptif kualitatif dengan menggunakan teknik observasi, wawancara, dan dokumentasi. Teknik analisis data yang digunakan adalah reduksi data, penyajian data, dan penarikan kesimpulan.  Hasil penelitian menunjukkan bahwa guru memandang penilaian autentik merupakan sistem penilaian yang Cukup Baik, dengan melakukan penilaian autentik dapat menilai kemampuan peserta didik secara keseluruhan, tidak hanya pada ranah pengetahuan peserta didik saja, tetapi juga pada ranah sikap dan keterampilan peserta didik. Faktor pendukung meliputi adanya motivasi, adanya kerjasama antar guru, terwujudnya lingkungan belajar yang kondusif, kesiapan peserta didik dalam pembelajaran, pemahaman dan penguasaan guru, kelengkapan sarana dan prasarana, pelatihan KKG, dukungan dari kepala sekolah dan pengawas sekolah. Faktor penghambat meliputi keterbatasan waktu dalam menilai, terlalu banyak perangkat pembelajaran yang harus di susun, kurangnya motivasi peserta didik dalam pembelajaran, adanya beberapa guru yang belum menguasai IT, kurangnya sosialisasi kurikulum 2013, kurangnya ketersediaan sarana dan prasarana.Kata Kunci: Authentic Assessment, Kurikulum 2013.